Inhibition of Dopamine Activity and Response of Rhipicephalus microplus Challenged with Metarhizium anisopliae - Victória Silvestre Bório; Thaís Almeida Corrêa; Jéssica Fiorotti; Emily Mesquita; Laura Nóbrega Meirelles; Mariana Guedes Camargo; Vânia Rita Elias Pinheiro Bittencourt; Patrícia Silva Golo (Journal of Fungi, 2022)
Dopamine modulates ticks and insect hemocytes and links these arthropods’ nervous and immune systems. For the first time, the present study analyzed the effect of a dopamine receptor antagonist on the survival, biological parameters, phagocytic index, and dopamine detection in the hemocytes of ticks challenged by Metarhizium anisopliae. The survival and egg production index of Rhipicephalus microplus were negatively impacted when ticks were inoculated with the antagonist and fungus. Five days after the treatment, the survival of ticks treated only with fungus was 2.2 times higher than ticks treated with the antagonist (highest concentration) and fungus. A reduction in the phagocytic index of hemocytes of 68.4% was observed in the group inoculated with the highest concentration of the antagonist and fungus compared to ticks treated only with fungus. No changes were detected in the R. microplus levels of intrahemocytic dopamine or hemocytic quantification. Our results support the hypothesis that dopamine is crucial for tick immune defense, changing the phagocytic capacity of hemocytes and the susceptibility of ticks to entomopathogenic fungi.